2002
DOI: 10.1093/emboj/21.3.377
|View full text |Cite
|
Sign up to set email alerts
|

Importins fulfil a dual function as nuclear import receptors and cytoplasmic chaperones for exposed basic domains

Abstract: -M.Mingot contributed equally to this work Many nuclear transport pathways are mediated by importin b-related transport receptors. Here, we identify human importin (Imp) 4b as well as mouse Imp4a, Imp9a and Imp9b as novel family members. Imp4a mediates import of the ribosomal protein (rp) S3a, while Imp9a and Imp9b import rpS7, rpL18a and apparently numerous other substrates. Ribosomal proteins, histones and many other nuclear import substrates are very basic proteins that aggregate easily with cytoplasmic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
291
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 300 publications
(317 citation statements)
references
References 36 publications
10
291
2
2
Order By: Relevance
“…Similarly, the BIB domain and the GR 407-525 fragment of GR bound to importin 7 in a HeLa cell extract ( Figure 3D, lanes 4 and 5), and mutation of GR 407-525 K513-515A again abrogated this interaction ( Figure 3D, lane 6). We conclude that GR can bind importin 7 and importin 8.Finally, consistent with other importin 7 and importin 8 substrates (Jakel and Gorlich, 1998;Dean et al, 2001;Jakel et al, 2002), the presence of a GTPase-deficient Ran mutant, RanQ69L, reduced the affinity of these import receptors for in vitro-transcribed and translated full-length GR ( Figure 3E, lanes 5 and 7), suggesting that these importins may import GR. In addition, RanQ69L reduced the binding observed between GST-importin ␣ and in vitro-transcribed and translated full-length GR ( Figure 3E, lane 3).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, the BIB domain and the GR 407-525 fragment of GR bound to importin 7 in a HeLa cell extract ( Figure 3D, lanes 4 and 5), and mutation of GR 407-525 K513-515A again abrogated this interaction ( Figure 3D, lane 6). We conclude that GR can bind importin 7 and importin 8.Finally, consistent with other importin 7 and importin 8 substrates (Jakel and Gorlich, 1998;Dean et al, 2001;Jakel et al, 2002), the presence of a GTPase-deficient Ran mutant, RanQ69L, reduced the affinity of these import receptors for in vitro-transcribed and translated full-length GR ( Figure 3E, lanes 5 and 7), suggesting that these importins may import GR. In addition, RanQ69L reduced the binding observed between GST-importin ␣ and in vitro-transcribed and translated full-length GR ( Figure 3E, lane 3).…”
supporting
confidence: 87%
“…Gorlich and colleagues (Jakel et al, 2002) have suggested that importin 7 and importin 8, among other import receptors, may bind exposed basic regions and act as cytoplasmic chaperones to prevent aggregation; conceivably, importin 7 and importin 8 might play a role in maintaining GR solubility during nuclear transport. It will be interesting to determine if importin 7 can import other proteins that carry NLSs similar to those on NL1 and the SV40 T-antigen (Fig- ure 1A), which are considered substrates of importin ␣.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that heterodimerization of Imp␤ with Imp7 is required for H1 import and that the simultaneous presence of both import receptors is not sufficient for import. Recently it has been shown that nuclear import of two ribosomal proteins (rpL4 and rpL6) also depends on this complex (26). However, the requirement for heterodimerization of the two import factors, as we have demonstrated here for H1 histones, has not been proven.…”
Section: Fig 5 Mapping Of the Imp␤ Binding Domain In Imp7mentioning
confidence: 51%
“…However, in addition to the results shown here, a growing body of evidence indicates that the Imp␤-Imp7 dimer is required as a chaperone and import receptor for nuclear proteins with extended very basic domains. A recent paper published by Jä kel et al (26) reports that import factors can prevent cytoplasmic aggregation of very basic proteins. The observation that the in vitro reconstitution of nucleosomes from isolated histones and DNA need molecular chaperones, called nucleosomal assembly proteins, and the fact that under physiological salt concentrations and without such factors, histones and DNA form aggregates and precipitate (31), also support the chaperone function of the Imp␤-Imp7 dimer.…”
Section: Fig 5 Mapping Of the Imp␤ Binding Domain In Imp7mentioning
confidence: 99%
See 1 more Smart Citation